Legal ladies : pioneers of law. Part 2 [videorecording (DVD)] - V., Gia (DocTV, 2023)
The documentary explores some of the most famous women who have made an impact on law and the legal system in America. From Ruth Bader Ginsburg to Erin Brockovich, get ready to spend some time with the women who have shaped history.